Facilitators’ views on content goals, learning obstacles, and teaching resources in reference to conditional probability - Griese, Birgit; Nieszporek, Ralf; Biehler, Rolf

Mathematik-Vorkurse zur Vorbereitung auf das Studium – Zielsetzungen und didaktische Konzepte - Lankeit, Elisa; Biehler, Rolf (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

The role of learning strategies for performance in mathematics courses for engineers - Liebendörfer, Michael; Göller, Robin; Gildehaus, Lara; Kortemeyer, Jörg; Biehler, Rolf; Hochmuth, Reinhard; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse

Data Science, Statistics, and Civic Statistics: Education for a Fast Changing World - Ridgway, Jim; Campos, Pedro; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

Mini-Aufgaben in mathematischen Übungsgruppen zur Analysis: Charakteristika von Aufgaben und Abstimmungsverhalten von Studierenden - Bauer, Thomas; Biehler, Rolf; Lankeit, Elisa (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Vorkurse und ihre Wirkungen im Übergang Schule – Hochschule - Lankeit, Elisa; Biehler, Rolf (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Dokumentation der Erhebungsinstrumente des Projekts WiGeMath - Schürmann, Mirko; Büdenbender-Kuklinski, C.; Lankeit, Elisa; Liebendörfer, Michael; Hochmuth, R.; Biehler, Rolf; Schaper, N.

Einführung in das WiGeMath-Projekt: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Ein Rahmenmodell für hochschuldidaktische Maßnahmen in der Mathematik - Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Profession-Specific Curriculum Design in Mathematics Teacher Education: Connecting Disciplinary Practice to the Learning of Group Theory - Wessel, Lena; Leuders, Timo (Practice-Oriented Research in Tertiary Mathematics Education)

From private digital platforms to public data spaces: implications for the digital transformation - Beverungen, Daniel; Hess, Thomas; Köster, Antonia; Lehrer, Christiane (Electronic Markets)
Technological developments such as Cloud Computing, the Internet of Things, Big Data and Artificial Intelligence continue to drive the digital transformation of business and society. With the advent of platform-based ecosystems and their potential to address complex challenges, there is a trend towards greater interconnectedness between different stakeholders to co-create services based on the provision and use of data. While previous research on digital transformation mainly focused on digital transformation within organizations, it is of growing importance to understand the implications for digital transformation on different layers (e.g., interorganizational cooperation and platform ecosystems). In particular, the conceptualization and implications of public data spaces and related ecosystems provide promising research opportunities. This special issue contains five papers on the topic of digital transformation and, with the editorial, further contributes by providing an initial conceptualization of public data spaces' potential to foster innovative progress and digital transformation from a management perspective.
Keywords: Digital transformation; Public data spaces; Digital platforms; GAIA-X

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Platform; Text mining; Machine learning; Data communications; Interpretive research; Systems design and implementation

Self-regulated learning in a mathematics course for engineers in the first semester: insights into students reported resource management and cognitive strategies - Kolbe, Tim; Wessel, Lena (Fourth conference of the International Network for Didactic Research in University Mathematics)

Mahr, Melanie: Reden ist Gold... – vom Umgang mit Sexualität bei Jugendlichen. Eine empirisch-qualitative Studie zur Situation der Sexualpädagogik im Kontext katholischer, vollstationärer Einrichtungen der Kinder- und Jugendhilfe. – Würzburg: Echter Verlag 2020 (=Studien zur Theologie und Praxis der Caritas und Sozialen Pastoral, 40) - Reis, Oliver (Theologische Revue)

Wann ist eine Differenz diskriminierend? Das Oszillieren zwischen Unterschieden und Ungleichheiten in der katholischen Gemeindearbeit - Hofmeister, Lisa; Reis, Oliver (Der Vielfalt Raum geben. Zum ambivalenten Potenzial einer differenzsensiblen Kirche)

Wie steht es mit der Situationsorientierung der Religionspädagogik? - Mellentin, Franziska; Reis, Oliver (unterwegs 2/2022)

Schulbuch - Rakowski, Jana; Reis, Oliver (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Vorlesen - Reis, Oliver; Saß, Katharina (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Kerze - Reis, Oliver; Wittke, Annika (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)